Fabrication and characterization of shape memory polyurethane porous scaffold for bone tissue engineering. Issue 4 (2nd February 2017) - Yu, Juhong; Xia, Hong; Teramoto, Akira; Ni, Qing‐Qing
Abstract: Tissue engineering is a promising alternative for treating bone defects. However, improvements in scaffold design are needed to precisely match the irregular boundaries of bone defects as well as facilitate clinical application. In this study, a shape memory polyurethane scaffold was fabricated using a salt‐leaching‐phase inverse technique. Different sizes of salts were used to obtain scaffolds with different pore sizes. Scanning electron microscope, X‐ray photoelectron spectroscopy, and X‐ray micro‐computed tomography analysis confirmed that three‐dimensional porous polyurethane scaffolds were obtained. The mechanical properties and biocompatibility of the scaffolds were analyzed by compression testing, thermal mechanical analysis, and cell experiments with osteosarcoma MG‐63 cells. The results revealed that the scaffolds had good mechanical properties and shape memory properties for bone repair, and also had the ability to promote cell proliferation. Thus, this scaffold design has good prospects for application to bone tissue engineering. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1132–1137, 2017.